Pengaruh Latihan Double Leg Bound Terhadap Peningkatan Eksplosive Power Otot Tungkai Pemain Bola Voli Di Klub Rajawali Vc Kota Bengkulu - Zahwa Oktadillah; Dody Ertanto; Dolly Apriansyah; Bihannudin Bihannudin (Educative Sportive, 2026)
This study aims to determine the effect of double leg bound training on increasing explosive leg muscle power in volleyball players at the Rajawali VC Club in Bengkulu City. A total sampling method was used, with 14 volleyball athletes from the Rajawali VC Club in Bengkulu City being selected as respondents. This experimental study employed a One Group Pretest-Posttest design, a pre-experimental design that included a pre-test (pre-treatment test) and a post-test (post-treatment test) within a single group. Data collection utilized test scores. Descriptive data analysis techniques and t-tests were used. The results of this study indicate an effect of double leg bound training on increasing explosive leg muscle power in volleyball players at the Rajawali VC Club in Bengkulu City, with a calculated t-value of 4.109 and a t-table of 1.725, with a significance level of α = 0.05 and df = 19.